Development of Controlled-Release Formulation to Improve Bioavailability of Esomeprazole (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The aim of this study was to release the active drug immediately after oral administration, to acquirequick, and enter systemic drug absorption. Such immediate-release products result in comparatively rapiddrug absorption and onset of associated pharmacodynamic effects. Materials and Methods: The preparedesomeprazole CR tablets were evaluated for the dissolution studies in acid buffer (pH-1.2) for 2 h, 4.5 pHacetate buffers for 2 h, 6.8 pH phosphate buffers for 8 h, and 7.4 pH phosphate buffers for 12 h % drugrelease that was calculated at various time intervals. Results and Discussion: The present study was aimedto developing controlled-release tablets of esomeprazole using various polymers. All the formulations wereevaluated for physicochemical properties and in vitro drug release studies. Conclusion: The current researchwork envisaged was an attempt to development of controlled-release formulations of esomeprazole to improvebioavailability.